A new galling insect model enhances photosynthetic activity in an obligate holoparasitic plant - Murakami, Ryo (Sci Rep, 2021)
Insect-induced galls are microhabitats distinct from the outer environment that support inhabitants by providing improved nutrients, defence against enemies, and other unique features. It is intriguing as to how insects reprogram and modify plant morphogenesis. Because most of the gall systems are formed on trees, it is difficult to maintain them in laboratories and to comprehend the mechanisms operative in them through experimental manipulations. Herein, we propose a new model insect, Smicronyx madaranus, for studying the mechanisms of gall formation. This weevil forms spherical galls on the shoots of Cuscuta campestris, an obligate parasitic plant. We established a stable system for breeding and maintaining this ecologically intriguing insect in the laboratory, and succeeded in detailed analyses of the gall-forming behaviour, gall formation process, and histochemical and physiological features. Parasitic C. campestris depends on host plants for its nutrients, and usually shows low chlorophyll content and photosynthetic activity. We demonstrate that S. madaranus-induced galls have significantly increased CO(2) absorbance. Moreover, chloroplasts and starch accumulated in gall tissues at locations inhabited by the weevil larvae. These results suggest that the gall-inducing weevils enhance the photosynthetic activity in C. campestris, and modify the plant tissue to a nutrient-rich shelter for them.